1988
DOI: 10.1128/iai.56.6.1567-1573.1988
|View full text |Cite
|
Sign up to set email alerts
|

Molecular size variations in an immunoprotective protein complex among isolates of Anaplasma marginale

Abstract: A major surface protein complex from the Florida isolate of Anaplasma marginale has been previously shown to induce protection in immunized cattle and has been proposed as the basis of a subunit vaccine against anaplasmosis. This complex in the Florida isolate is composed of two noncovalently associated polypeptides with molecular masses of 105 and 100 kilodaltons (kDa). The analogous protein complex from four geographically different isolates of A. marginale was immunoprecipitated and compared with the protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 18 publications
1
29
1
Order By: Relevance
“…To prepare antigen for in vitro assays, the sonicate was diluted in phosphate-buffered saline (PBS; pH 7.4) containing 25 g/ml of the protease inhibitors, antipain, and E-64 (Boehringer Mannheim, Indianapolis, IN) and 300 g/ml phenylmethylsulfonyl fluoride (Sigma Chemical Co., St. Louis, MO). Native MSP2 was purified essentially as described [20,21]. Briefly, pelleted A. marginale were resuspended in electrophoresis sample buffer and separated on multiple preparative sodium dodecyl sulfate gradient (10 -20%) polyacrylamide gels.…”
Section: Preparation Of a Marginale And Msp2 Antigensmentioning
confidence: 99%
“…To prepare antigen for in vitro assays, the sonicate was diluted in phosphate-buffered saline (PBS; pH 7.4) containing 25 g/ml of the protease inhibitors, antipain, and E-64 (Boehringer Mannheim, Indianapolis, IN) and 300 g/ml phenylmethylsulfonyl fluoride (Sigma Chemical Co., St. Louis, MO). Native MSP2 was purified essentially as described [20,21]. Briefly, pelleted A. marginale were resuspended in electrophoresis sample buffer and separated on multiple preparative sodium dodecyl sulfate gradient (10 -20%) polyacrylamide gels.…”
Section: Preparation Of a Marginale And Msp2 Antigensmentioning
confidence: 99%
“…MSP-5 was originally identified in outer membrane preparations of the Norton Zimbabwe strain and subsequently shown to be conserved in other strains, including Florida (31). MSP-1 is a complex of two polypeptides with molecular masses of 105 and 100 kDa (4), designated MSP-la and MSP-lb, respectively (18). MSP-la exhibits marked size polymorphism among different strains of A. marginale (18) and is encoded by a single-copy gene (2).…”
mentioning
confidence: 99%
“…MSP 1 through 5 have been identified and information on the gene sequences, recombinant protein analogs, monospecific and monoclonal antibodies, isolate variability, and potential value in diagnostic assays and vaccines are available. [28][29][30][31][32][33]19,[34][35][36][37][38][39][40][41][42] MSP1 has been shown to confer partial protection in immunized cattle against A. marginale challenge, and to contain an epitope recognized by monoclonal antibodies capable of in vitro neutralization of isolated rickettsia. 38 MSP1a varies in size among different geographic isolates, but the neutralization-sensitive epitope is conserved.…”
Section: Development Of a Recombinant Or Synthetic Vaccinementioning
confidence: 99%
“…38 MSP1a varies in size among different geographic isolates, but the neutralization-sensitive epitope is conserved. 35 Sequencing of the MSP1a gene of different isolates and characterization of this epitope using synthetic peptides demonstrated that the neutralization-sensitive epitope was located on a tandem 28 or 29 amino acid repeat of the MSP1a. 30 The number of tandem repeats varies between isolates of A. marginale .…”
Section: Development Of a Recombinant Or Synthetic Vaccinementioning
confidence: 99%